A framework for conceptualizing leadership in conservation. Issue 5 (21st September 2022) - Webb, Seth A.; Bruyere, Brett; Halladay, Matt; Walker, Sarah
Abstract: Conservation challenges occur in complex social-ecological systems that require scientists and practitioners to recognize and embrace that humans are active agents within these systems. This interdependence of the social and ecological components of systems necessitates effective leadership to address and solve conservation problems successfully. Although conservation practitioners increasingly recognize leadership as critical to achieve conservation goals, clarity about the term leadership remains elusive in terms of specific strategies and behaviours. Our objective in this review of conservation leadership scholarship was to build on prior literature to conceptualize and define the behavioural leadership strategies that lead to successful conservation outcomes. Following an initial review of more than 1, 200 peer-reviewed publications, we conducted a systematic review of 59 articles utilizing an inductive analysis approach and identified a set of five leadership domains that contribute to positive conservation outcomes: (1) stakeholder engagement, (2) trust, (3) vision, (4) individual champion, and (5) excellence in internal attributes. Each domain is defined by 2–4 behaviours that we consider leadership practices. To sustain meaningful progress toward global conservation of biodiversity, conservation scientists and practitioners must embrace and invest in leadership as an integral component of solving our collective conservation challenges.